Perancang Aplikasi Media Pembelajaran Informatika Kelas IX Berbasis Web Di SMP Islam Al Azhar 39 Bukittinggi - Sadar Martua Haholongan Sir; Liza Efriyanti; Fahrul Hadi (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2025)
Education is an important means of effort because it helps the development of an individual's affective, cognitive, and psychomotor aspects. To achieve effective learning, learning media that can deliver material in an interesting way and facilitate learning experiences are needed. This study aims to design a web-based learning media application for the Informatics subject in grade IX at SMP Islam Al Azhar 39 Bukittinggi that is valid, effective, and practical. The learning media application was designed using HTML (HyperText Markup Language) programming language to produce an attractive and more interactive learning media application. The method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Testing was carried out by validators using a quantitatively processed questionnaire. The test results showed that the developed application obtained a validity score of 93.5% (highly valid), a practicality score of 92% (highly practical), and an effectiveness score of 88% (highly effective). Thus, the application is suitable for use in the Grade IX Informatics learning process.